Urban transportation: A case study on bike-sharing usage in Klang Valley - Wahab, Siti Norida; Sham, Rohana; Amir Hussin, Amir Aatieff; Ismail, Shakerin; Rajendran, Salini Devi (ExcelingTech Publisher, 2018)
The principal aim of this paper is to empirically investigate the bike-sharing usage among Klang Valley citizen. Data for this study were collected using an online questionnaire survey. However, due to the low responses, simulations have been used and applied to predict the outcomes of the research. The simulated data was generated based on a uniform selection of a random element that simulated the answers of the potential questionnaire respondents. We limited the number of responses to 350 respondents. Correlation analysis was applied to analyze the data collected. The factors affecting the bike-sharing usage are availability, safety, convenience cost and enjoyment. Convenience is found as the only variable that influences the bike-sharing usage among Klang Valley citizen. The findings contribute towards an understanding of factors that may encourage people to shift from an automobile to bike-sharing as an alternative towards a sustainable transportation option. In theoretical contribution, the developed theoretical framework presents a platform for future empirical bike-sharing studies and extend previous research conducted in Western countries. This research shows that bike-sharing is important in embracing non-motorized means of transport towards reducing the environmental pollution and acknowledgement towards the reduction in road congestion, accidents, and other social and environmental problems. Findings from this study will help practitioners implement strategies with greater potential in increasing the attractiveness of bike-sharing and improve the sustainability of land use and transportation systems.